Percentage change in the INPC, food basket and minimum wage in Mexico, January 2002-June 2020 - Ayllon Benítez, Julio César; Omaña Silvestre, José Miguel; Sangerman-Jarquín, Dora Ma.; Martínez Damián, Miguel Ángel; Matus Gardea, Jaime Arturo; González Razo, Felipe de Jesús (Revista Mexicana de Ciencias Agrícolas, 2021)
In Mexico, the National Council for the Evaluation of Social Development Policy uses the term income poverty, for this purpose it uses the minimum welfare line, which refers to people whose income is insufficient to acquire the recommended basic basket, equivalent to the value of the food basket per person and that of the welfare line, similar to the previous denomination of patrimonial poverty, equivalent to the value of the food and non-food basket per person per month. Constitutionally, the minimum wage must cover the needs of a family in the material, social and cultural aspect and to provide education. The study period was from January 2002 to June 2020. The information was processed in the statistical program SAS®. The objective of this paper was to estimate the percentage change rate of the national consumer price index, prices of the rural and urban food basket and of general minimum wage to explain the differential between the latter and verify its effect when being above or below the percentage change of the national consumer price index and the VPPCA. In episodes of high inflation, mainly in the food aspect, periods 2004, 2007-2009, 2012-2013 and 2017, the SMG barely compensated part of the increase, with the panorama accentuating in 2017; however, significant increases that occurred since 2015 and in recent periods (2019 and 2020) in the nominal SMG by 16 and 20% have been important in reducing the gap between the real SMG.
Keywords: economy; minimum wage; prices; vulnerability